Inkulturasi Dan Tata Perayaan Ekaristi 2020 Gambaran Berinkulturasi dalam Konteks Indonesia - Emanuel Pranawa Dhatu Martasudjita (Litbang STFT Widya Sasana Malang, 2022)
Sacramentary 2020 helps create a new prayer dynamic as well as challenge for Catholics particularly in our Eucharistic celebrations. It was approved by the Indonesian Bishop Conferences (KWI) on December 27, 2020. Indonesian Sacramentary is a fruit of inculturation in Indonesia. The question to be answered: is sacramentary a fruit of inculturaltion? A method employed in this article is a qualitative one. It particularly uses library studies, guided by theories of inculturation as a continuous process. Furthermore, in this method the Gospel is proclaimed and reflected into its socio-political as well as cultural-religious environment while gradually transforming people and its society. This research shows indeed that Sacramentary 2020 has well-reflected an inculturation into an Indonesian context. Sacramentary 2020 is the fruit of a long and ongoing process of liturgical inculturation by the Indonesian Catholic Church. Since Eucharistic celebration is the culmination and central in our Christian life, the process of inculturation of the Sacramentary 2020 reflects the dynamic of inculturation of the Indonesian Church. This inculturation process involved the faithful of all level, from hierarchy to religious men and women, various experts as well as the people of God in general.